2005
DOI: 10.1021/ma051802n
|View full text |Cite
|
Sign up to set email alerts
|

Poly(Phenylene-pyridyl) Dendrimers:  Synthesis and Templating of Metal Nanoparticles

Abstract: A new family of poly(phenylene-pyridyl) dendrimers (up to the fourth generation) with different periphery was synthesized via a divergent route by using a cascade of Diels-Alder cycloadditions. Tetra(4-ethynylphen-1-yl)methane served as a core. A new A 2B cyclopentadienone building block, namely, pyridine-containing cyclopentadienone with protected dienophile functions was prepared. By varying the building blocks at the last step of dendrimer construction, one could design molecules possessing either a phenyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 38 publications
(69 reference statements)
2
58
0
Order By: Relevance
“…In addition to PAMAM, dendrimers based on propyleneimine [28], ethyleneimine [29], diaminobutane [30] phosphorus-containing [31], and phenylene-pyridyl units [32] have been used to prepare dendrimer/noble metal nanoparticle composites. More recently, Astruc and coworkers developed an interesting family of dendrimers ( Figure 5) synthesized by click reaction and applied them as templates and hosting agents for Pd NPs [33,34].…”
Section: Figurementioning
confidence: 99%
“…In addition to PAMAM, dendrimers based on propyleneimine [28], ethyleneimine [29], diaminobutane [30] phosphorus-containing [31], and phenylene-pyridyl units [32] have been used to prepare dendrimer/noble metal nanoparticle composites. More recently, Astruc and coworkers developed an interesting family of dendrimers ( Figure 5) synthesized by click reaction and applied them as templates and hosting agents for Pd NPs [33,34].…”
Section: Figurementioning
confidence: 99%
“…15, 16 The structures of the studied samples were confirmed by the data of NMR spectroscopy, MALDI TOF mass spectrometer, and elemental analysis data. 15 The structures of dendrimers G1 8Py, G2 24Py, G3 42Py, and G4 90Py are presented above and below.…”
Section: Methodsmentioning
confidence: 99%
“…15 A BKT 3 completely automated adiabatic vacuum calorim eter designed and produced at the Termis joint stock closed com pany (Mendeleevo, Mosocow Region) was used for the study of the temperature dependence of heat capacity С p° = f(T) of the samples at 6-300 K. Liquid helium and nitrogen were used as cooling agent. Ampules with substances were filled with dry he lium (as a heat exchange gas) to a pressure of 4 kPa at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…matic dendrimers and their complexation with metals, DNA, drugs, and other compounds were investigated at length [247][248][249][250][251][252][253][254][255][256][257][258][259]. It was found that these com pounds show promise for many fields, for example, for the delivery of genes, the encapsulation of nanoparti cles by dendrimers, and the manufacture of dual action preparations.…”
Section: Dendrimersmentioning
confidence: 99%